ダイ 6 ジ ナンキョク チイキ カンソクタイ チキュウ カガク ブモン ホウコク - 綿抜, 邦彦; ワタヌキ, クニヒコ; WATANUKI, Kunihiko (国立極地研究所, 1963)
P(論文) Geochemical researches were carried out on board the "SOYA" and in the Ongul Islands. Sea water was collected to make chemical analysis every day at 9:30 a.m. The radioactivity of rain, snow and sea ice were measured by G-M counter. The results were depicted in Table 1. The rain which was collected in the vicinity of Tokyo has radioactivity; 1100c.p.m./l or so. And the rain which was collected near the equator has no radioactivity. We could not detect the radioactivity of the snow in the Antarctic icy region. Pool water and puddle water were collected in the environs of the Ongul Islands. The results were represented in Table 2. The maximum temperature of the pool water was 15.2℃. We collected wind-borne salt with wet gauze,and also salt samples which were found on the rock: some were white and others were yellowcolored. Some rocks were also collected in the pegmatite region. departmental bulletin paper